Because of Eva : A Jewish Genealogical Journey - Gordon, Susan J., 1943- (Book collections on Project MUSE., 2016)
"In Because of Eva, an American Jewish woman travels to Eastern Europe and Israel to solve mysteries in her family's past by delving into World War II and Holocaust history. What began as a seemingly simple search for "Eva," the elderly relative who had signed Gordon's grandfather's death certificate in New York long ago, became a journey of discovery when Gordon found her in Tel Aviv. There, she heard Eva's stories of survival during the Holocaust, especially in Nazi-occupied Budapest. Eventually, Gordon would retrace Eva's steps in Budapest and visit ancestral towns in Ukraine to bear witness to the slaughter of entire populations of Jews. Amid remnants of loss and destruction in the small town where her grandfather was born, Gordon also uncovered details of her family's world before relatives immigrated to America. Gordon's journey into her past provided the deep sense of connection and belonging she needed as an adult child of divorce and abuse. Gaining insight about her family's history, Gordon reconciles issues of betrayal and loyalty, and finally finds her place in Judaism. Part memoir, part detective story, Because of Eva is an intimate tale of one woman's history within the epic sweep of world events in the twentieth century."--Publisher's website